Management Strategy of the East Lombok Tourism Service in Increasing Interest in Visiting Tourists in Tete Batu Village - Irwan Yon Hadi; Lalu A. Hery Qusyairi; Lalu Wira Bhakti (Pendidikan Al-Gafari, 2023)
A tour is an activity carried out by someone or a group somebody with visit a place for objective recreation. development private, or learn uniqueness Power pull visited tours in period time Meanwhile, tourism is also a whole related activity with tourism and nature multidimensional. Study This aims to know the service strategy of tourism to increase interest in visiting tourists in Tete Batu Village, East Lombok. Service strategy Tourism Lombok East plays a big role as a motivator, facilitator, and dynamist in realizing the enhancement of visiting tourists as well as the welfare of the community in Tete Batu village. So from Thus the department's strategy for tourism is immediately optimal and deep For building a society capable of making Tete Batu become a tourist world. The type of research carried out is study qualitative with a approach descriptive where is the data obtained? through observation, interviews, and documentation. As for the informants in the study, this is one of the heads and secretary service East Lombok tourism, field marketing prawisata, head of Tete Batu Village, chairman pokdarwis, and perpetrators of business Tete Batu Village tour. Research results show that service strategy tourism increases amount tourists. Pre-tourism department do strategy marketing where marketing strategy Has various method including online media promotions, events, exhibitions, banners, and brochures. Enhancement motivation by giving training to society. The Tourism Department empowers the society around Tete Batu village by giving direction and socialization in making souvenirs.